Pleomorphic Adenoma of the Palate: Diagnostic and Surgical Strategy - Ciré Ndiaye; Mame Sanou Diouf; Houra Ahmed; Arame Thiam; Ngoné Diaba Diop; Aminata Mbaye; Mamadou Woury Barry; Mame Diarra Bousso Ba (Case Reports in Otolaryngology)
Pleomorphic adenoma is a benign tumor of the salivary glands. It develops preferentially in the parotid gland. The authors report a localization of a pleomorphic adenoma on the palate and discuss the value of CT scan in therapeutic strategy.